The Metaphor of the Metaphor in the Chapter on the Letter ha from Lisan al-Arab by Ibn Manzur (d. 711 AH): A Semantic Study - Rashid, Saad Ali (Journal of Tikrit University for Humanities, 2024)
This research addresses the topic of (the metaphor of metaphor) in an analytical study of the words in which it is permissible more than once in the chapter on the ha from Lisan al-Arab by Ibn Manzur (d. 711 AH). The research has shown that Lisan al-Arab dictionary includes many words that can be described as metaphors. We find that the author of the dictionary often looks at the words and explains their origin, and the metaphors and semantic transfer that occurred in them, through signs indicating metaphor. This indicates that the ancient linguists - even if they did not declare the term - paid attention to this semantic issue, which is the metaphor of the metaphor, through their tracking of the connotation of words and what they denote in use, and this is what the study tried to confirm by monitoring examples of the metaphor.